Collective Action Model: Facing Temporary Loss Income while the Rubber Replanting Program. Issue 1 (September 2020) - Novra, Ardi; Suparjo
Abstract: The research objective was to design a collective action model in the context of household independence in overcoming the temporary loss income (TLI) period during the rubber replanting process. The research partner was the Sumber Rezeki Farmer Group (SRFG) in Mestong District, Jambi, Indonesia. The results showed that collective action in integrated waste processing to produce TCI and BA+ can work well but not followed by inter-cropping cultivation implementation. The BA+ prototype technology with capacity 1, 100 liters/period more advantages over conventional methods because it only takes 18 days with clearer and loss of pungent odor. The substitution power of food crops was only 49, 27% from potential temporary loss income with the highest in food-corn which's 55.83%. Conversely, the food crops productivity implemented was not targeted as achieved by planting demonstration plot scale. The main inhibiting factor the water availability which is highly dependent on the season, and animal wild pest attacks such as monkeys and wild boar. Based on the results it can be concluded that the collective action model had not been effective at the implementation stage so that further research is needed to address the water management and wild animal pests control problems.